Edukasi Dan Pelatihan Mengelola Stress Dalam Pengasuhan Anak - Sainah, Sainah; Irmawati, Irmawati; Sofyan, Muhammad (Patria Artha Journal of Community (PKM), 2025)
Parenting is a crucial responsibility for parents that often causes stress, especially for mothers who juggle multiple roles. Poorly managed parenting stress can negatively impact parents' mental health, parenting styles, and child development. Recognizing this issue, a team of midwifery/nursing lecturers and students conducted a community service activity targeting parents at the Flamboyan Integrated Health Post (Posyandu) in the Green Nurhidyat Housing Complex, within the Samata Community Health Center (Puskesmas) working area of Gowa Regency. The activity included counseling on parenting stress, training in simple relaxation techniques, group discussions to share experiences, and brief mentoring for participants in need. Additionally, modules and leaflets were distributed as educational resources for ongoing use. The results of the activity demonstrated an increase in participants' knowledge about the concept of parenting stress, skills in practicing relaxation techniques, and changes in attitudes toward greater patience and self-confidence. Participants also agreed to establish a communication forum to provide social support for the program's sustainability. Overall, this activity successfully increased parents' capacity to manage parenting stress and made a significant contribution to improving family well-being, while strengthening the role of higher education institutions in community empowerment.